Incarcerated inguinal hernias surgical treatment specifics in elderly patients - Pešić Ivan; Karanikolić Aleksandar; Đorđević Nebojša; Stojanović Miroslav; Stanojević Goran; Radojković Milan; Nestorović Milica (Vojnosanitetski Pregled, 2012)
Background/Aim. Incarcerated inguinal hernias surgical treatment represents one of the most frequent surgical treatments in elderly patients. The percentage of incarcerated inguinal hernias urgent surgical treatments is growing exponentially with the age in patients over 50. The aim of the study was to investigate some of the factors that may have impact on the incarcerated inguinal hernias surgical treatment outcome in elderly patients. Methods. The study included 180 patients classified in two groups: the study group (> 65 years of age) and the control group (≤ 65), managed in the period from January 2005 till March 2009 at the General Surgery Clinic, Clinical Center Niš. Results. Most of the patients had right inguinal hernia (52.6%, the study group; 59.1%, the control group). All the study group patients suffered from some of accompanying chronic diseases (100%), opposite to 39 (59%) patients of the control group. Synthetic material was implanted in 124 (68.9%) patients, while the tension technique was performed in 65 (31.1%) patients. The duration of incarceration more than 24 h (p = 0.015), previous abdominal surgery (p = 0.001), the American Society of Anesthesiologists physical status classification system (ASA classification) (p = 0.033) and the presence of chronic diseases (p = 0.01) appeared to be statistically significant risk factors for performing intestinal resection in the study group, while in the control group they represented risk factors, but not at the level of statistical significance (p <0.05), except for the duration of incarceration (p = 0.007). A higher ASA stage (p = 0.001) and the presence of bowel resection (p <0.001) are the most important risk factors for lethal outcome in both groups of patients. Conclusion. Incarcerated inguinal hernia in elderly patients is a serious problem. A higher ASA score and the presence of bowel resection are the most important factors related to unfavorable outcome.